Stimulatory and Toxic Effects of Neurotransmitters on the lux Operon-Dependent Bioluminescence of Escherichia coli K12 TGI - Elena V. Sorokina ,; Ilya R. Vodolazov ,; Alexander V. Oleskin, (Journal of Pharmacy and Nutrition Sciences, 2019)
Background: The normal functioning of the brain requires neuromediators, i.e., substances that transmit messages between nervous cells. Neurochemicals also function as signals that are involved in communication among the microorganisms that inhabit the human organism. While the impact of “classical” neurotransmitters including catecholamines, serotonin, and histamine on microorganisms has been investigated in a number of recent publications, this work provides evidence for the stimulatory and inhibitory (toxic) effects of some other important neurochemicals that have not received sufficient attention in the literature. Methods: The biosensor was based on a GM Escherichia coli K12 strain (TGI) that contained the lux operon of the luminescent soil bacterium Photorhabdus luminescencens ZMI. The biosensor was exposed to the action of the tested neurotransmitters for 15 mins to 144 hrs. The intensity of bacterial luminescence (counts / second) was monitored in the control and the experimental samples with an 1251 BioOrbit luminometer (Finland). Results: Neurochemicals such as putrescine, acetylcholine, taurin, and indole were found to stimulate, at low concentrations (0.1-10 µM), the luminescence of the strain E. coli K12 TGI containing the lux operon from Photorhabdus luminescencens ZMI. At higher concentrations, putrescine, taurin, and indole exerted a weak toxic influence, i.e. they marginally attenuated the luminescence of E. coli K12 TGI. Conclusions: Based on the data obtained, a regulatory, presumably receptor-dependent, effect is exerted by the tested neurochemicals on the bacterium E. coli K12 TGI, in an analogy to their impact on nervous, immune, and other specialized types of eukaryotic cells. However, high neurochemical concentrations are likely to produce nonspecific effects on the bacterial luciferase system and/or on membrane phosphorylation.